2007
DOI: 10.2136/sssaj2006.0155
|View full text |Cite
|
Sign up to set email alerts
|

Major Biogeochemical Processes in Soils‐A Microcosm Incubation from Reducing to Oxidizing Conditions

Abstract: Six soils used for rice (Oryza sativa L.) production were incubated using an automatic microcosm system. Production of trace gases (CO2, CH4, and N2O) and transformation of N, S, and metals (Fe and Mn) were studied in soil suspensions incubated from reducing to oxidizing conditions. Results show that soil pH variation was inversely correlated to soil redox potential (EH) change (P < 0.01). Soil CO2 production exponentially increased with soil EH increase. In contrast, soil CH4 production and DOC showed an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(88 citation statements)
references
References 49 publications
4
82
1
1
Order By: Relevance
“…They all possess ubiquinones in their respiratory chains that cause the more rapid degradation of the various substrates offered during the incubation experiments (e.g., carbohydrates and polymeric compounds) in comparison with the deeper horizons. These results are consistent with other studies reporting that soil respiration (expressed as soil CO 2 production) rose exponentially with increasing redox potential (Yu et al 2007). Still, switching to an anaerobic milieu did not cut off, but only slowed down, carbon turnover of the substrates offered in the BIOLOG plates accompanied by a shift in the utilized substrates (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…They all possess ubiquinones in their respiratory chains that cause the more rapid degradation of the various substrates offered during the incubation experiments (e.g., carbohydrates and polymeric compounds) in comparison with the deeper horizons. These results are consistent with other studies reporting that soil respiration (expressed as soil CO 2 production) rose exponentially with increasing redox potential (Yu et al 2007). Still, switching to an anaerobic milieu did not cut off, but only slowed down, carbon turnover of the substrates offered in the BIOLOG plates accompanied by a shift in the utilized substrates (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Liu et al (2012b) and Zhang et al (2012) observed this reduction of emission in rice paddy field experiments. It is known that during the flooding period, when the soil solution reaches highly reductive conditions, the NO 3 -concentration is reduced (Yu et al, 2007). Under these conditions, denitrifying bacteria use N 2 O as N source and reduce it to molecular nitrogen (N 2 ) (Chapuis-Lardy, 2007), a process, that may even result in influx (negative flux) of N 2 O. Biochar could play a role in this process, for example by immobilizing nitrate from the soil solution.…”
Section: Determining Factors and Potential Effects Of Biochar On Soilmentioning
confidence: 99%
“…Soil Eh will change greatly during the soil wetting-drying processes (Cornu et al 2007;Yamaguchi et al 2011;Shaheen et al 2014a, b). Studies find that DOC concentration usually decreases with increasing soil Eh (Grybos et al 2007;Yu et al 2007;Frohne et al 2014). Possible mechanism during the soil wetting-drying cycles may be related to the following two aspects.…”
Section: Changes In Soil Solution Docmentioning
confidence: 98%
“…Inversely, the forms of Fe/Al/Mn-(hydr) oxides may complex with the DOC from the soil solution when the soil is in oxidizing conditions. In addition, changes in soil Eh conditions may also occur with a possible shift in microbial community composition (Drenovsky et al 2004), and the microbial activities can also decrease soil solution DOC by releasing soluble organic metabolites or enhance DOC by microbial carbon consumption (Chow et al 2006;Yu et al 2007). The hydrolysis of dead microorganisms and soil organic matter by microbial consumption will increase the DOC (125 to 100 % WHC), while the increasing numbers of new microorganisms will consume DOC and may result in a decrease in DOC when the soil is dried from 100 to 50 % WHC.…”
Section: Changes In Soil Solution Docmentioning
confidence: 99%